Thymopentin improves the survival of septic mice by promoting the production of 15-deoxy-prostaglandin J2 and activating the PPARγ signaling pathway - Zhang, Ye (2020)
Sepsis, a systemic inflammatory response syndrome (SIRS) caused by infection, is a major public health concern with limited therapeutic options. Infection disturbs the homeostasis of host, resulting in excessive inflammation and immune suppression. This has prompted the clinical use of immunomodulators to balance host response as an alternative therapeutic strategy. Here, we report that Thymopentin (TP5), a synthetic immunomodulator pentapeptide (Arg-Lys-Asp-Val-Tyr) with an excellent safety profile in the clinic, protects mice against cecal ligation and puncture (CLP)-induced sepsis, as shown by improved survival rate, decreased level of pro-inflammatory cytokines and reduced ratios of macrophages and neutrophils in spleen and peritoneum. Regarding mechanism, TP5 changed the characteristics of LPS-stimulated macrophages by increasing the production of 15-deoxy-Δ12,14-prostaglandin J2 (15-d-PGJ2). In addition, the improved effect of TP5 on survival rates was abolished by the peroxisome proliferator-activated receptor γ (PPARγ) antagonist GW9662. Our results uncover the mechanism of the TP5 protective effects on CLP-induced sepsis and shed light on the development of TP5 as a therapeutic strategy for lethal systemic inflammatory disorders.